Infinite conditions on the road to peace: the second New Labour government's foreign policy approach to the Israeli–Palestinian conflict after 9/11. Issue 1 (2nd January 2019) - Nelson, Ian
ABSTRACT: This article examines how a resurgent clash of Arab and Israeli nationalisms created tensions within New Labour as the leadership sought to reconcile claims of duplicity in its Middle East policy after 9/11 while retaining party unity and an international consensus for a war in Afghanistan. It argues that as European and international pressure to prioritise Middle East peace before pursuing a war with Iraq increased, Tony Blair's emphasis on economic progress as a prerequisite to creating a state of Palestine was expanded to determine that Palestinian national rights also be considered on the evidence of fundamental reform and modernisation across the spectrum of political, civil and cultural life. These objectives, however, were not to be achieved following the deployment of a UN peace-keeping force, but the prevailing conditions of the Israeli occupation, provisos later inscribed in the US-led goal-driven, performance-based Road Map for Peace. This focus ran in parallel with his assumed role as a transatlantic 'bridge', and collectively helped to transform the multilateralist template of the Quartet into a classic trilateralist negotiating model—bilateral Arab-Israel talks, unilaterally overseen by the US—enacting the further exclusion of key European partners.